CouQual: assessing overall service quality in courier service industry and the moderating impact of age, gender and ethnicity. (2016) - Valaei, Naser; Rezaei, Sajad; Shahijan, Milad Kalantari
Considering the moderating impact of age, gender and ethnicity on consumer behaviour, the purpose of this study is to investigate courier service quality elements and the impact of perceived service quality on overall service quality. A total of 561 valid questionnaires were collected to empirically assess measurement and structural model using partial least square (PLS) path modelling approach. Our results imply that promptness, safety and convenience are the main contributors while accuracy and tangibility do not positively contribute to perceived service quality. In addition, perceived service quality positively influences overall service quality and ethnicity moderates overall service quality but age and gender do not moderate overall service quality. This study is among a few attempts to examine courier service quality elements in Malaysia. Contributions, practical implications and limitations are discussed.